2016
DOI: 10.1007/s00415-016-8123-2
|View full text |Cite
|
Sign up to set email alerts
|

A novel clinical tool to classify facioscapulohumeral muscular dystrophy phenotypes

Abstract: Based on the 7-year experience of the Italian Clinical Network for FSHD, we revised the FSHD clinical form to describe, in a harmonized manner, the phenotypic spectrum observed in FSHD. The new Comprehensive Clinical Evaluation Form (CCEF) defines various clinical categories by the combination of different features. The inter-rater reproducibility of the CCEF was assessed between two examiners using kappa statistics by evaluating 56 subjects carrying the molecular marker used for FSHD diagnosis. The CCEF class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
71
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 67 publications
(73 citation statements)
references
References 24 publications
1
71
0
1
Order By: Relevance
“…Each registered patient provided consent for use of their data for research. To verity the previous observations that patients with the B1 phenotype have a less severe form of the disease than patients with the typical FSHD (A) phenotype, we determined whether clinical differences in disease severity could also be detected among patients in the UK FSHD Patient Registry by analyzing the self‐reported distribution of weakness and current motor function. We divided the patients into 2 groups according to phenotype: group 1, classic FSHD phenotype/category A of CCEF and group 2, facial sparing phenotypes/category B1 of CCEF.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Each registered patient provided consent for use of their data for research. To verity the previous observations that patients with the B1 phenotype have a less severe form of the disease than patients with the typical FSHD (A) phenotype, we determined whether clinical differences in disease severity could also be detected among patients in the UK FSHD Patient Registry by analyzing the self‐reported distribution of weakness and current motor function. We divided the patients into 2 groups according to phenotype: group 1, classic FSHD phenotype/category A of CCEF and group 2, facial sparing phenotypes/category B1 of CCEF.…”
Section: Methodsmentioning
confidence: 99%
“…Infantile and late‐onset cases are not uncommon; clinical severity and sequence of involvement in different muscle groups can vary . The Italian Clinical Network for FSHD has recently proposed a new FSHD Comprehensive Clinical Evaluation Form (CCEF) that defines nine clinical categories designed to capture clinical diversity . Among these categories, category B1 identifies patients with an incomplete FSHD phenotype not fulfilling the clinical diagnostic criteria of FSHD, showing scapular muscle weakness with or without lower limb involvement but always without facial muscle weakness.…”
mentioning
confidence: 99%
“…Previously, several studies have shown that the FSHD-related D4Z4 contractions were found not only in patients with the classic FSHD form but also in patients with a variety of atypical phenotypes or overlapping syndromes, including the facial-sparing form (SHD), distal myopathy, asymmetric brachial weakness or limb-girdle muscular dystrophy (LGMD) [6][7][8][9]. Based on this clinical variability, the Comprehensive Clinical Evaluation Form (CCEF) proposed by Ricci et al was used to categorize FSHD patients with typical or atypical form [10]. However, the precise mechanism has not been clear.…”
Section: Introductionmentioning
confidence: 99%
“…115 Facioscapulohumeral muscular dystrophy (FSHD1) is the third most common muscular dystrophy and presents from infancy to older adult age. 116,117 The pattern of muscle involvement is typically asymmetric and characterized by progressive weakness and atrophy of the facial, shoulder, upper arm, axial, and proximal leg muscles. 118,119 More severe infantile forms can also present with rapid progression of weakness, marked hyperlordosis, sensorineural hearing loss, and retinal vasculopathy.…”
Section: Imaging and Pathological Correlationsmentioning
confidence: 99%